Enhancing FAPbI3 perovskite solar cell performance with a methanesulfonate-based additive - Foong, Joseph Japheth Yeow Wan (2024)
We present a strategy to simultaneously enhance the efficiency and stability of perovskite solar cells by introducing a new pseudo-halide additive based on formamidinium methanesulfonate (FAMeSf). The optimal additive concentration of 2 mol% leads to improved efficiency of over 21% and superior stability of unencapsulated cells for over 3000 hours of storage time under near-ambient conditions. Our results highlight the importance of additive engineering in boosting the performance of FAPbI3 perovskite solar cells.